EVALUASI KESESUAIAN LAHAN UNTUK BUDIDAYA PERIKANAN TAMBAK DI PESISIR KENDAL (Geo-Image, 2013)
Carelessness in determining the location of ponds and pond management is not only a huge waste but also affect the fish production. This research is aimed at assessing the characteristics of coastal land in Kendal with the application of geographic information systems technology (GIS) and analyzing land suitability classes aquaculture in the coastal region of Kendal. Study sites are located in the coastal region of Kendal district that includes seven sub-districts namely Kaliwungu, Brangsong, Kendal Town, Patebon, Cepiring, Watercress, and Rowosari. Analysis of the data used is the method of scoring. The variables in this study were: (1) land slope, (2) soil texture, (3) soil pH, (4) land use, (5) precipitation, (6) accessibilities, (7) the distance from the river, (8) the distance from the sea. The results showed that in the coastal region of Kendal, there are 3 variations of land suitability classes for the pond that is highly suitable class (S1) area of 2076.2 ha, according to the class (S2) 19,606,3 ha and the area is quite appropriate class (S3) there is an area of 2817, 1 ha. Dominant factor affecting the growth of the pond is that it contains high salts